2004
DOI: 10.1002/pi.1424
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene‐co‐vinyl acetate copolymer crosslinking through ester–alkoxysilane exchange reaction catalyzed by dibutyltin oxide: mechanistic aspects investigated through model compounds by multinuclear NMR spectroscopy

Abstract: It was shown that the crosslinking of ethylene‐co‐vinyl acetate (EVA) copolymer by a tetraalkoxysilane in molten state, in the temperature range 100–250 °C, was obtained only in the presence of dibutyltin oxide. At this temperature EVA pendant ester groups readily react with dibutyltin oxide to give a dimeric 1‐alkoxy‐3‐acetoxytetrabutyldistannoxane distributed along the polymer chains. The exact role of this tin compound in the ester–alkoxysilane reaction was elucidated through reactions of the tetraalkoxysil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…[8][9][10] Common ways of EVA crosslinking involve (i) macroradical formation via thermal decomposition of organic peroxides, [11] (ii) high-energy irradiation (γ-ray or electron beam), [12] and (iii) compounding with alkoxysilane coupling agents that form organic/inorganic network-structures via transesterifications of vinyl acetate moieties in EVA. [13,14] Each method has its own distinct advantages depending on the applications and environments. The last crosslinking technology has been developed by Bounor-Legaré et al [14] and has recently been attracting much attention because the organic/inorganic hybrid materials offer the opportunity to combine the desirable properties of organic polymers (toughness and elasticity) with those of inorganic moieties (hardness, heat, and chemical resistance).…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] Common ways of EVA crosslinking involve (i) macroradical formation via thermal decomposition of organic peroxides, [11] (ii) high-energy irradiation (γ-ray or electron beam), [12] and (iii) compounding with alkoxysilane coupling agents that form organic/inorganic network-structures via transesterifications of vinyl acetate moieties in EVA. [13,14] Each method has its own distinct advantages depending on the applications and environments. The last crosslinking technology has been developed by Bounor-Legaré et al [14] and has recently been attracting much attention because the organic/inorganic hybrid materials offer the opportunity to combine the desirable properties of organic polymers (toughness and elasticity) with those of inorganic moieties (hardness, heat, and chemical resistance).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Bounor-Legare et al [18] extended this type of catalysis to ester/alkoxysilane exchange reactions between polymer-ester pendant groups and a tetraalkoxysilane giving access to hybrid crosslinked materials easily obtained during processing. In this case, the reactions with model compounds have shown that the catalytic efficiency was due to very efficient exchanges between alkoxy groups of catalytic exo tin sites and the alkoxy silane crosslinking agent.…”
Section: Resultsmentioning
confidence: 98%
“…In the presence of ester and amide groups, DBTO reacts with ester and amide groups through insertion of [SnO] link at elevated temperatures as shown in Scheme , generating the distannoxane intermediate species, 1‐alcoxy‐3‐acyloxytetrabutyldisannoxane (A, B), which acts as the catalytic species for the exchange reaction between free ester or amide groups and distannoxane, and finally leads to the exchange reaction of ester and amide groups. The reaction mechanism for the ester–amide exchange reaction between PA6 and EVM is proposed in Scheme .…”
Section: Resultsmentioning
confidence: 99%